Highly enantio- and diastereoselective reactions of γ-substituted butenolides through direct vinylogous conjugate additions - Zhang, Wen (2013)
The strength of the weak: An L-tert-leucine-derived amine–thiourea catalyst (see scheme, green box) promotes the asymmetric vinylogous conjugate addition reaction between γ-aryl- and alkyl-substituted butenolides with the butenamides and enoates shown. Computational studies show the preference for the observed stereochemistry is a result of favourable weak non-bonding interactions, which stabilize the transition state.